Priorities in effective management of primary health care institutions in Lithuania: Perspectives of managers of public and private primary health care institutions - Budrevičiūtė, Aida (PLoS One, 2018)
BACKGROUND: Primary health care institutions are looking for opportunities to create value for patients and to increase the competitiveness of the health care institution. Determination of competitive priorities for creation of value for patients in the management of primary health care institutions allows improving competitiveness and achieving a competitive advantage in the market. THE AIM OF THE STUDY: To determine the priorities in the management of public and private primary health care institutions by using the focus group discussion method with managers. METHODS: The study was exploratory with intention to find a ground for a management theory and to be the root for the development of health care reform in Lithuania. Focus group discussions were held in 10 Lithuanian counties; 10 focus group sessions were carried out. A total of 48 primary health care executives were interviewed. The participants of this qualitative study were given 8 questions related to value creation of the primary health care institution to patients and rise in competitiveness. The main question of the focus group discussion was “What are the main priorities of management of primary health care institution?” The criteria of data collection based on the deep understanding of the phenomenon and the richness of data expressed by participants of the research. RESULTS: Qualitative research showed that the priorities of management of primary health care institutions were work management of an organization; human resources management; patient management; and health policy decision making. The participants of focus groups pointed out that effective work of primary health care institutions is ensured by the model of management, doctor-patient communication, quality and timely delivery of health care services, and financial resources. The major decisions involving the management of patients were as follows: meeting patients’ expectations, quality and timely satisfaction of patients’ needs, effective solution of patients’ problems, patient-centered services, patient satisfaction, and communication with the patient. Accessibility to services, quality, geographical accessibility, disease prevention, strengthening of patients’ health and adequate funding were mentioned as the priorities of health policy.